Individual, school‐related and family characteristics distinguish co‐occurrence of drinking and depressive symptoms in very young adolescents. (29th June 2015) - Salom, Caroline L.; Kelly, Adrian B.; Alati, Rosa; Williams, Gail M.; Patton, George C.; Williams, Joanne W.
Abstract: Introduction and Aims: Alcohol misuse and depressed mood are common during early adolescence, and comorbidity of these conditions in adulthood is associated with poorer health and social outcomes, yet little research has examined the co‐occurrence of these problems at early adolescence. This study assessed risky and protective characteristics of pre‐teens with concurrent depressed mood/early alcohol use in a large school‐based sample. Design and Methods: School children aged 10–14 years ( n = 7289) from late primary and early secondary school classes in government, Catholic and independent sectors participated with parental consent in the cross‐sectional Healthy Neighbourhoods Study. Key measures included depressed mood, recent alcohol use, school mobility, family relationship quality, school engagement and coping style. Multinomial logistic regression analyses were used to identify school and family‐related factors that distinguished those with co‐occurring drinking and depressive symptoms from those with either single condition. Gender and school‐level interactions for each factor were evaluated. Results: Co‐occurring conditions were reported by 5.7% of students [confidence interval (CI)95 5.19, 6.19]. Recent drinkers were more likely than non‐drinkers to have symptoms consistent with depression (odds ratio 1.80; CI95 1.58, 2.03). Low school commitment was associated with co‐occurring drinking/depressive symptoms (odds ratio 2.86; CI95 2.25, 3.65 compared with null condition). This association appeared to be weaker in the presence of adaptive stress‐coping skills (odds ratio 0.18; CI95 0.14, 0.23). Conclusions: We have identified factors that distinguish pre‐teens with very early co‐occurrence of drinking and depressed mood, and protective factors with potential utility for school‐based prevention programmes targeting these conditions. [Salom CL, Kelly AB, Alati R, Williams GM, Patton GC, Williams JW. Individual, school‐related and family characteristics distinguish co‐occurrence of drinking and depressive symptoms in very young adolescents. Drug Alcohol Rev 2016;35:387–396]